Nicholas Nickleby - Herdon, Tim (Dominoes., 2010)
Left penniless by the death of his improvident father, young Nicholas Nickleby assumes responsibility for his mother and sister and seeks help from his Scrooge-like Uncle Ralph. Instantly disliking Nicholas, Ralph sends him to teach in a school run by the stupidly sadistic Wackford Squeers. Nicholas decides to escape, taking with him the orphan Smike, one of Squeers's most abused young charges, and the two embark on a series of adventurous encounters with an array of humanity's worst and best -- greedy fools, corrupt lechers, cheery innocents, and selfless benefactors. Though one of Dickens's earliest works, Nicholas Nickleby features many of his familiar trademarks : a long, complex plot full of surprising twists, unexpected revelations, and jaw-dropping coincidences; a crowded cast of colorful (and memorably named) characters, among them Vincent Crummles, Newman Noggs, and Sir Mulberry Hawk; and an emotionally potent mix of wildly exuberant comedy, deeply moving melodrama, and passionate social criticism fueled by Dickens's own childhood experiences of poverty and injustice.